EFFORTS OF BINMAS UNITS THROUGH EMPOWERMENT OF SECURITIES TO MAINTAIN CONDUCTIVE COMMUNITY SECURITY AND ORDER - NAVA NUR DIANTI (Police Studies Review, 2022)
ABSTRACT EFFORTS OF BINMAS UNITS THROUGH EMPOWERMENT OF SECURITIES TO MAINTAIN CONDUCTIVE COMMUNITY SECURITY AND ORDER Nava Nur Arrafah Dianti, 18.237, navadianti123@gmail.com The background of this problem arises because of the lack of conducive public security and order, especially in the Kudus Police Legal Area. The development of Pam Swakarsa, especially the Security Guard or Security Unit to carry out the duties of the National Police in their Work Environment. This study aims to describe how the Security Guards Empowerment is carried out by the Kudus Polres Binmas Unit and how the Binmas Unit's efforts are to increase the security guard empowerment, as well as what factors influence the implementation of security guard empowerment. The theories and concepts in this writing are POAC Management Theory and 6 M, and SWOT Analysis, while the concepts used are the Binkamsa concept, the concept of the Perpol Security Unit No. 4 of 2020, the Concept of Effort, the Concept of Maintaining community security and order, and the Conducive concept. This writing method is a Qualitative Approach and Field Research (Field Research). Primary and Secondary data sources. Data collection techniques with interviews, observations, and documents. The location is in the Kudus Police Legal Area. Validity by Triangulation. Data analysis with data reduction, data presentation, and conclusion drawing. With this research, it is hoped that it can be used as a reference for carrying out tasks, especially the Binmas Unit of the Kudus Police in improving the maintenance of a conducive community security and order. Keywords : Efforts, Binmas Unit, Empowerment of Security Guards, Public Order and Safety.